Atrial fibrillation and heart failure due to reduced versus preserved ejection fraction: A systematic review and meta-analysis of death and adverse outcomes - Kotecha, Dipak; Chudasama, Rajiv; Lane, Deirdre A.; Kirchhof, Paulus; Lip, Gregory Y.H. (International journal of cardiology, 2016)
Atrial fibrillation (AF) and heart failure frequently coexist, commonly resulting in serious adverse events. With both conditions increasing in prevalence and justified concerns about treatment efficacy, it is vital to understand how the type of heart failure impacts on prognosis. We performed a systematic review of studies examining cardiovascular outcomes in AF patients with heart failure and reduced ejection fraction (AF-HFrEF) compared to those with preserved ejection fraction (AF-HFpEF). The primary outcome was all-cause mortality, meta-analyzed using a random-effects model. Prospective registration: PROSPERO-CRD42014007305. Thirteen studies were included in the systematic review (n=54,587) with 10 suitable for meta-analysis, including retrospective/prospective cohorts and sub-group analyses of randomized trials. AF-HFrEF was present in 49% and these patients were younger, more often male and with higher NYHA class than AF-HFpEF. Oral anticoagulation use was 55% versus 50% respectively (p<0.001). All-cause mortality was significantly higher in AF-HFrEF; risk ratio (RR) 1.24, 95% CI 1.12–1.36, p<0.001 (n=45,100), with absolute death rates of 24% compared to 18% in AF-HFpEF over 2years. There were no significant differences in incident stroke (RR 0.85, 95% CI 0.70–1.03, p=0.094; n=33,773) or heart failure hospitalization (RR 1.21, 95% CI 0.96–1.53, p=0.115; n=31,583). The risk of bias was generally low, but heterogeneity was substantial. All-cause mortality is significantly higher in AF patients with HFrEF compared to HFpEF, although stroke risk and heart failure hospitalization are similar. Further studies are needed to address the prevention of adverse outcomes in all AF patients with heart failure, regardless of ejection fraction.